UJI EFEKTIVITAS PRIMING DENGAN BEBERAPA KONSENTRASI EKSTRAK KUNYIT TERHADAP DAYA SIMPAN BENIH KEDELAI (Glycine max (L.) Merrill) - Dewi Junita; Syamsuddin Syamsuddin; Hasanuddin Hasanuddin (Jurnal Agrotek Lestari, 2020)
Soybeans are staple food after rice and corn. Deterioration of soybeans seed during storage caused by soybeans composed of high lipid.  This study was conducted to investigate the effectivity of priming with various concentration turmeric extract on reduce deterioration soybeans seed during storage. The experiment was arranged in non factorial Complete Randomized Design (CRD) with four levels of turmeric extract concentration treatment, (control, 25%, 50% and 75%.).  The ageing process accelerated by subjecting the seeds to high temperature and relative humidity in a chamber (Deluche methods). Germination and vigour were evaluated periodically. The result showed that priming with turmeric extract could increase vigour and germination under ageing conditions. The 25% concentration  extract showed the  higher value of seed vigour than other concentration. Keywords : Soybeans, priming, turmeric extract, storage period.